(untitled) (Community Based Medical Journal, 2016)
Generalised granuloma annulare is a benign inflammatory dermatosis characterized by dermal papules and annular plaques. It is often clinically confused with other dermatoses particular superficial fungal infection. A man of 50 years came with multiple erythematous, mildly pruritic, firm papules and annular skin lesion over the extremites and back of trunk for the last two years. He was treated with an oral antifungal for several months under diagnosis of tinea corporis without remission. The diagnosis of Generalised Granuloma Annulare was made based on skin biopsy and histopathological examination. Oral Acitretin and topical tacrolimus (0.1%) were administered and after 1 month of follow up period the lesion were started to regress. Complete remission was found after 3 months treatment. CBMJ 2016 July: Vol. 05 No. 02 P: 39-42